Shape-controllable plano-convex lenses with enhanced transmittance via electrowetting on a nanotextured dielectric. Issue 39 (2nd September 2016) - Li, Xiangmeng; Li, Xiangming; Shao, Jinyou; Tian, Hongmiao; Jiang, Chengbao; Luo, Yu; Wang, Li; Ding, Yucheng
Abstract : Millimetre-scale plano-convex lenses with controllable focal lengths are presented via irreversible electrowetting of UV-curable polymer droplets on a nanotextured dielectric. Abstract : Millimetre-scale plano-convex lenses with controllable focal lengths are presented via electrowetting UV-curable polymer droplets on a nanotextured dielectric. A large range of numerical aperture is achieved. Such plano-convex lenses can be peeled off and transferred to other substrates. The lenses with nanocavities on the bottom surfaces exhibit enhanced transmittance.